Porous silicon nitride loaded Pd-M catalyst, preparation thereof and application of porous silicon nitride loaded Pd-M catalyst in selective hydrogenation of acetylene
By using porous silicon nitride-supported Pd-M catalyst in acetylene selective hydrogenation reaction, the existing Pd-based catalysts have been solved, and efficient catalytic performance and long-life catalysts have been achieved.
Patent Information
- Application Number
- CN202411966551.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The existing Pd-based catalysts have short lifetime, poor stability and high cost of use in acetylene selective hydrogenation reaction.
The porous silicon nitride-supported Pd-M catalyst is used to adjust the geometry and electronic structure of the Pd nanoparticles by introducing the second component additive metal M (such as Cu, Zn, Ag, etc.), and improve the catalytic performance and stability of the catalyst.
High catalytic activity and selectivity in acetylene selective hydrogenation reaction are achieved, extending the life of the catalyst and reducing the cost of use.
Smart Images

Figure HDA0005218493670000011
Abstract
Description
Technical Field
[0001] The invention relates to a porous silicon nitride supported Pd-M catalyst, preparation thereof and application thereof in selective hydrogenation of acetylene. Background Art
[0002] Selective hydrogenation of acetylene is an important process for removing acetylene impurities in industrial ethylene production. Even a very small amount of acetylene can cause the polymerization catalyst to deactivate. Therefore, the acetylene content must be reduced to below 5ppm and converted into ethylene as much as possible. At present, Pd-based catalysts are the most commonly used catalysts in industrial acetylene hydrogenation, with the characteristics of high acetylene conversion rate and moderate reaction temperature. Since Pd has good activity and stability for hydrogen and good affinity for carbon-carbon triple bonds, it exhibits good low-temperature catalytic activity in acetylene semi-hydrogenation reactions. However, the active component Pd of the Pd-based catalyst is easy to aggregate, and the adsorption of C2H2 on the bridging Pd site is stronger than the π-type adsorption on the isolated Pd atom, resulting in excessive hydrogenation of C2H2 to generate C2H6, which causes low selectivity and carbon deposition problems, making it difficult to maintain a high ethylene selectivity, and the catalyst life is also short. Modifying the geometry or electronic structure of palladium-based catalysts and controlling the size, morphology and distribution of palladium nanoparticles through the interaction between palladium nanoparticles and additives and carriers are the keys to improving the activity, selectivity and durability of palladium catalytic hydrogenation. Although the use of traditional metal oxides (such as Al2O3) as carriers can improve the dispersibility of Pd nanoparticles, it is still challenging to synthesize highly dispersed nanoparticles with uniform size and the same coordination structure through traditional methods.
[0003] Silicon nitride (Si3N4) belongs to the hexagonal system and can be divided into two crystal forms: α-Si3N4 and β-Si3N4. Si3N4 has the advantages of good mechanical strength, thermal conductivity, stable chemical properties, low thermal expansion coefficient, high hardness and relative inertness. In the field of high-temperature materials, it has excellent properties such as anti-oxidation, corrosion resistance and thermal shock resistance, and is increasingly valued by people. Its cost is relatively low, the separation efficiency (especially for particles in the range of 0.1 to 100μm) is high, and it has biocompatibility. Si3N4 is widely used in the field of ceramics to manufacture high-performance ceramic products; in the electronics industry, it can be used as a heat dissipation material and insulating components; in the field of mechanical manufacturing, it is often used for wear-resistant components; in the metallurgical industry, it can also be used as a refractory material. In addition, these excellent properties of Si3N4 make it have extremely high application value in the fields of national defense and military industry, semiconductor thermal conductive substrates, biomedicine and new technologies. At present, silicon nitride is generally used as a catalyst carrier in the field of catalysis.
[0004] Commercial silicon nitride is usually composed of low-temperature (1200°C) α-Si3N4 or high-temperature (1500°C) β-Si3N4, produced by grinding the body ceramic to produce a low specific surface area (usually less than 10m 2 / g) of powder, which may limit the loading amount of the catalyst and the number of active sites. In addition, pure Si3N4 has problems such as limited surface properties and weak interaction with the catalyst, which makes the reliability of pure silicon nitride in catalytic reactions not guaranteed. Therefore, improving its reliability has always been an important direction of Si3N4 research. CN 116273136 A discloses a Cu / silicon nitride catalyst and its preparation method and its application in CO catalytic oxidation. CN 114433246 A discloses a silicon nitride carrier with high specific surface area and its preparation method, which is used to prepare a highly dispersed transition metal catalyst anchored in silicon nitride, and the catalyst is used for CO hydrogenation to alcohol reaction. However, there is no report on the application of silicon nitride in the selective hydrogenation reaction of acetylene.
[0005] Therefore, it is necessary to develop a preparation method to introduce the second component promoter metal M into Pd-based catalysts to adjust the geometric and electronic structures of Pd nanoparticles and produce a synergistic effect to improve the catalytic performance of the catalyst. Summary of the invention
[0006] The purpose of the present invention is to provide a porous silicon nitride supported Pd-M catalyst and its preparation and application in the selective hydrogenation of acetylene, so as to overcome the problems of short life, poor stability and high cost of use of the existing Pd-based catalysts used in the selective hydrogenation reaction of acetylene. When the porous silicon nitride supported Pd-M catalyst is used in the catalytic reaction of selective hydrogenation of acetylene, it shows excellent catalytic performance and stability.
[0007] The technical solution adopted by the present invention is described in detail below.
[0008] In a first aspect, the present invention provides a method for preparing a porous silicon nitride supported Pd-M catalyst, wherein the M is selected from at least one of Cu, Zn, Ag, Ni, Cr, and Ru, and the preparation method comprises the following steps:
[0009] 1) Obtaining porous silicon nitride: mixing silicon nitride powder with a binder, an auxiliary agent and a solvent, kneading, and then extruding, air-drying, cutting, drying and calcining to obtain porous silicon nitride; the binder is selected from one or more of polyvinyl alcohol, polyethylene glycol, carboxymethyl cellulose and methyl cellulose; the auxiliary agent is selected from one or more of glycerol, starch, urea, wet titanic acid (titanic acid containing hydrated molecules), ammonium carbonate, citric acid and nitric acid; the solvent is deionized water; the mass ratio of Si3N4 powder, binder, auxiliary agent and solvent is 40-60:1-10:1-10:30-55;
[0010] 2) fully mixing the M-containing precursor with palladium chloride, the porous silicon nitride obtained in step 1), and solvent A, and stirring evenly to obtain a mixture 1;
[0011] 3) leaving the mixture 1 obtained in step 2) to stand until the solution becomes clear and transparent, filtering to obtain a mixture 2;
[0012] 4) subjecting the mixture 2 obtained in step 3) to microwave heating and drying to obtain a drying product;
[0013] 5) subjecting the dried product obtained in step 4) to high temperature treatment using a Joule heater, cooling to room temperature, and washing with solvent B to obtain a high temperature treated product;
[0014] 6) The high temperature treatment product obtained in step 5) is subjected to microwave heating and drying, and ground to obtain a porous silicon nitride supported Pd-M catalyst.
[0015] The porous silicon nitride powder obtained in step 1) of the present invention has a certain geometric shape, a certain mechanical strength and a pore structure. The present invention uses a binder to knead the silicon nitride powder so that the silicon nitride powder is bonded into a certain shape, thereby achieving the purpose of enhancing its mechanical strength, so that the silicon nitride molded product after the silicon nitride powder is molded has a certain geometric shape. The present invention uses an auxiliary agent to bond the silicon nitride powder into a certain shape, while making the silicon nitride material have a good pore structure, ensuring that the silicon nitride material has a high specific surface area and good pore connectivity.
[0016] Preferably, the method for preparing porous silicon nitride comprises the following steps:
[0017] Step a: Weigh a certain amount of commercial silicon nitride powder and a binder, mix them evenly, add an auxiliary agent and a solvent and knead them;
[0018] Step b: Extruding the kneaded product obtained in step a into a long strip through an extruder;
[0019] Step c: placing the strips obtained in step b at room temperature for preliminary drying and then cutting them into strips of a certain length;
[0020] Step d: drying the strip obtained in step c;
[0021] Step e: placing the dried sample in step d in a Joule heating apparatus, calcining at a temperature of 350 to 1000° C. for 1 to 10 hours to obtain porous silicon nitride.
[0022] As a further preference, in step b), the extruded cylindrical strip has a diameter of 1.5 to 3 mm; and in step c), the strip has a length of 3 to 4 mm.
[0023] As a further preference, the drying process in step d) is carried out in a microwave oven at a drying temperature of 80 to 120° C. and a drying time of 10 to 24 hours.
[0024] As a further preference, the molar ratio of N:Si in the commercial silicon nitride is 4:3.
[0025] Preferably, in step 2), the copper-containing precursor is selected from one or more of copper acetate, copper chloride, copper nitrate and copper sulfate; the zinc-containing precursor is selected from one or more of zinc oxide, zinc chloride, zinc acetate, zinc carbonate, zinc nitrate and zinc sulfate; the silver-containing precursor is selected from one or more of silver nitrate, silver oxide, silver sulfate, silver chloride, silver ammonia solution and silver acetylacetonate; the nickel-containing precursor is selected from one or more of nickel chloride, nickel nitrate, nickel carbonate, nickel hydroxide, nickel oxalate and nickel sulfate; the chromium-containing precursor is selected from one or more of sodium chromate, potassium chromate, chromium chloride and chromium sulfate; the rhodium-containing precursor is selected from one or more of rhodium chloride, rhodium nitrate and rhodium acetylacetonate.
[0026] Preferably, the M-containing precursor, palladium chloride and porous silicon nitride in step 2) are added according to an element molar ratio of M:Pd:N=1:1:0.5-5.
[0027] Preferably, the solvent A in step 2) is selected from water, methanol, ethanol, acetone, sucrose aqueous solution, and starch aqueous solution.
[0028] Preferably, the mixture in step 3) is allowed to stand at a temperature of room temperature to 90° C. for a time of 0.5 to 3 hours.
[0029] Preferably, the microwave heating and drying frequency in step 4) is 2.45 GHz, the processing temperature is 60-150° C., the vacuum degree is 100-100000 Pa, and the time is 2-20 h.
[0030] Preferably, the temperature of the high temperature treatment in step 5) is 300-1800° C., the time of the high temperature treatment is 1-30 hours, and the atmosphere of the high temperature treatment is an inert atmosphere, specifically helium, argon or nitrogen.
[0031] Preferably, the solvent B in step 5) is selected from at least one of deionized water, hydrogen peroxide, methanol, ethanol, propanol, cyclohexanol, butanol, acetone, liquid ammonia and aqueous ammonia.
[0032] Preferably, the microwave heating and drying frequency in step 6) is 2.45 GHz, the treatment temperature is 60-150° C., the vacuum degree is 100-100000 Pa, and the time is 2-20 h.
[0033] Furthermore, the grinding in step 6) is grinding into powder of 10-200 mesh, which can be pressed into blocks according to needs to produce different particle sizes.
[0034] In a second aspect, the present invention provides a porous silicon nitride supported Pd—M catalyst prepared according to the preparation method described in the first aspect.
[0035] In a third aspect, the present invention provides use of the porous silicon nitride supported Pd-M catalyst described in the second aspect in the selective hydrogenation of acetylene to ethylene.
[0036] The selective hydrogenation of acetylene to ethylene is specifically implemented as follows: the porous silicon nitride-supported Pd-M catalyst is loaded into a fixed bed reactor, a raw gas containing hydrogen and acetylene is introduced, the reaction temperature is set at 150-300° C., and the reaction pressure is set at 0.1-0.5 MPa, so that acetylene and hydrogen react to generate ethylene.
[0037] Furthermore, in the raw material gas, n(H2) / n(C2H2)=0.8-1.2 / 1. Furthermore, the raw material gas also contains carrier gas and C2H4, and the carrier gas is nitrogen.
[0038] Furthermore, during the reaction, the acetylene gas space velocity is controlled to be 30 to 370 h -1 .
[0039] Compared with existing catalysts, the acetylene hydrogenation catalyst provided by the present invention has the following beneficial effects:
[0040] (1) The preparation method of the catalyst of the present invention is to synthesize in situ porous silicon nitride supported Pd-M catalyst, and the catalyst itself has excellent activity. Among them, the porous Si3N4 prepared by the present invention has good mechanical strength and good pore structure, so that the Si3N4 material has a high specific surface area, good pore connectivity and high structural stability.
[0041] (2) During the preparation process, the porous silicon nitride supported Pd-M catalyst can controllably adjust the physicochemical properties of the catalyst by adjusting the precursor, Si3N4 and solvent.
[0042] (3) The porous silicon nitride supported Pd-M catalyst of the present invention is prepared by using a microwave oven for heating, which is energy-saving and efficient, has uniform heating, is easy to operate, and has easily controllable conditions. It is also helpful in obtaining a high-purity product, thereby expanding its scope of application.
[0043] (4) During the preparation process of the porous silicon nitride supported Pd-M catalyst of the present invention, a Joule heater is used to treat the material at high temperature, which has the advantages of rapid response, high repeatability, precise control, clean and environmental protection, high energy utilization rate and good stability.
[0044] (4) The Pd-M / Si3N4 material of the present invention has many advantages. The dispersion of the catalyst is significantly improved. The introduction of the additive M promotes the dispersion of metal Pd and inhibits the agglomeration of Pd species during the reaction, which has a high research value.
[0045] (5) The Pd-M / Si3N4 catalyst of the present invention has good reaction activity in the above-mentioned acetylene hydrogenation reaction. After 100 hours of reaction, the acetylene conversion rate can reach a maximum of more than 92.5%, and the ethylene selectivity can reach a maximum of more than 99%. BRIEF DESCRIPTION OF THE DRAWINGS
[0046] Figure 1 1 is the adsorption-desorption curve and pore size distribution diagram of the porous silicon nitride prepared in Example 1. DETAILED DESCRIPTION
[0047] The present invention is described below with specific examples. It is necessary to point out that the examples are only used to further illustrate the present invention, but cannot be understood as limiting the scope of protection of the present invention, and the present invention is not limited thereto in any way. Those skilled in the art in this field can make some non-essential improvements and adjustments based on the content of the above invention.
[0048] The polymer used in the embodiment of the present invention is: polyvinyl alcohol CAS: 9002-89-5; the molecular weight of starch is 342;
[0049] The Si3N4 powder used in the present invention is purchased from a commercial source. Properties: powdery, with a specific surface area of 49 m 2 / g, off-white, average particle size 1μm, β-phase crystal.
[0050] If no specific conditions are specified in the examples of the present invention, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be obtained by conventional technical means or purchased commercially.
[0051] Example 1
[0052] (1) Commercial Si3N4 powder, polyvinyl alcohol, glycerol, and deionized water are mixed and kneaded in a certain mass fraction ratio of Si3N4 powder: polyvinyl alcohol: glycerol: deionized water = 50:5:5:50; the obtained kneaded product is extruded into cylindrical strips with a particle size of 2 mm by an extruder; the obtained cylindrical strips are initially dried at room temperature and then cut into 3 mm long particles; the obtained long particles are dried at 80°C for 10 h in a microwave oven with a vacuum degree of 1000 Pa; the dried sample is calcined at 350°C for 2 hours using a Joule heater to obtain porous silicon nitride; the porous silicon nitride has a compressive strength of 35 N / cm and a specific surface area of 175 m 2 / g, the most probable pore size is 100nm, the pore volume is 0.35mL / g, and the crystal structure is anatase;
[0053] (2) Weigh 9.13 g of copper acetate, 8.865 g of palladium chloride, and 7 g of porous silicon nitride, add 10 ml of deionized water, and stir for 2 h to mix thoroughly;
[0054] (3) placing the mixture at 60° C. for 1 h, and filtering the solution until it becomes clear and transparent to obtain a mixture;
[0055] (4) subjecting the mixture to microwave heating and drying at 110° C. and 10,000 Pa for 2 h;
[0056] (5) The dried mixture was heated at 10 °C min-1 using a Joule heater under a nitrogen atmosphere. -1 The heating rate was increased to 1100℃ for high temperature treatment for 2h;
[0057] (6) Cooling the treated catalyst to room temperature and washing it three times with deionized water;
[0058] (7) The washed catalyst was subjected to microwave heating and drying at 110° C. and 10,000 Pa for 2 h, and the particle size was ground to 20 mesh;
[0059] (8) Evaluation of acetylene hydrogenation reaction in a fixed bed reactor: Acetylene hydrogenation reaction at 220°C, acetylene space velocity 120h -1 , the reaction was carried out under the condition that the volume ratio of hydrogen to acetylene was 1:1.2, the raw gas also contained a carrier gas and C2H4, and the carrier gas was nitrogen (the volume ratio of hydrogen to acetylene to nitrogen to ethylene was 1:1.2:200:100); after the reaction, the catalyst performance was that the initial acetylene conversion rate was 70%, the ethylene selectivity was 99%, and after 100 hours, the initial acetylene conversion rate dropped to 63%, and the ethylene selectivity was maintained at 99%.
[0060] Example 2
[0061] (1) Commercial Si3N4 powder, polyvinyl alcohol, glycerol, and deionized water are mixed and kneaded in a certain mass fraction ratio of Si3N4 powder: polyvinyl alcohol: glycerol: deionized water = 40:1:1:30; the obtained kneaded product is extruded into cylindrical strips with a particle size of 1.5 mm by an extruder; the obtained cylindrical strips are placed at room temperature for preliminary drying and then cut into 3 mm long particles; the obtained long particles are dried at 90°C for 12 h in a microwave oven with a vacuum degree of 1000 Pa; the dried sample is calcined at 400°C for 1 hour using a Joule heater to obtain porous silicon nitride; the porous silicon nitride has a compressive strength of 32 N / cm and a specific surface area of 165 m 2 / g, the most probable pore diameter is 95nm, the pore volume is 0.38mL / g, and the crystal structure is anatase type.
[0062] (2) Weigh 5.378 g of copper chloride, 7.0928 g of palladium chloride, and 4.2 g of porous silicon nitride, add 12 ml of deionized water, and stir for 1.5 h to mix thoroughly;
[0063] (3) placing the mixture at 90° C. and standing for 0.5 h, until the solution becomes clear, filtering to obtain a mixture;
[0064] (4) subjecting the mixture to microwave heating and drying at 80° C. and 1000 Pa for 12 h;
[0065] (5) The dried mixture was heated at 10°C min-1 using a Joule heater in a helium atmosphere. -1 The heating rate was increased to 1300℃ for high temperature treatment for 2.5h;
[0066] (6) cooling the catalyst after the high temperature treatment to room temperature and washing it three times with ethanol;
[0067] (7) The washed catalyst was subjected to microwave heating and drying at 80° C. and 1000 Pa for 12 h, and the particle size was ground to 30 mesh;
[0068] (8) Evaluation of acetylene hydrogenation reaction in a fixed bed reactor: Acetylene hydrogenation reaction at 200 °C, acetylene space velocity 100 h -1 , the reaction was carried out under the condition that the volume ratio of hydrogen to acetylene was 1:1, the raw gas also contained a carrier gas and C2H4, and the carrier gas was nitrogen (the volume ratio of hydrogen to acetylene to nitrogen to ethylene was 1:1:202:100); after the reaction, the catalyst performance was that the initial acetylene conversion rate was 95%, the ethylene selectivity was 99%, and after 100 hours, the initial acetylene conversion rate dropped to 92%, and the ethylene selectivity was maintained at 99%.
[0069] Example 3
[0070] (1) Commercial Si3N4 powder, carboxymethyl cellulose, starch, and deionized water are mixed and kneaded in a certain mass fraction ratio of Si3N4 powder: carboxymethyl cellulose: starch: deionized water = 60:10:10:55; the obtained kneaded product is extruded into cylindrical strips with a particle size of 2.5 mm by an extruder; the obtained cylindrical strips are placed at room temperature for preliminary drying and then cut into 3.5 mm long particles; the obtained long particles are dried at 100°C for 14 h in a microwave oven with a vacuum degree of 1000 Pa; the dried sample is calcined at 500°C for 3 hours using a Joule heater to obtain porous silicon nitride; the porous silicon nitride has a compressive strength of 34 N / cm and a specific surface area of 177 m 2 / g, the most probable pore diameter is 103nm, the pore volume is 0.41mL / g, and the crystal structure is anatase type.
[0071] (2) Weigh 5.63 g of copper nitrate, 5.32 g of palladium chloride, and 5.6 g of porous silicon nitride, add 8 ml of methanol, and stir for 1.5 h to mix thoroughly;
[0072] (3) The mixture was allowed to stand at room temperature for 3 h, and when the solution became clear, it was filtered to obtain a mixture;
[0073] (4) subjecting the mixture to microwave heating and drying at 60° C. and 5000 Pa for 10 h;
[0074] (5) The dried mixture was heated at 10 °C min-1 using a Joule heater under an argon atmosphere. -1 The heating rate was increased to 300 °C for 4 h;
[0075] (6) cooling the catalyst after the high temperature treatment to room temperature and washing it three times with methanol;
[0076] (7) subjecting the washed catalyst to microwave drying at 60° C. and 5000 Pa for 10 h, and grinding the catalyst to a particle size of 50 mesh;
[0077] (8) Evaluation of acetylene hydrogenation reaction in a fixed bed reactor: Acetylene hydrogenation reaction at 180 °C, acetylene space velocity 30h -1 , the reaction was carried out under the condition that the volume ratio of hydrogen to acetylene was 0.8:1, the raw gas also contained a carrier gas and C2H4, and the carrier gas was nitrogen (the volume ratio of hydrogen to acetylene to nitrogen to ethylene was 0.8:1:202:100); after the reaction, the catalyst performance was that the initial acetylene conversion rate was 99%, the ethylene selectivity was 99%, and after 100 hours, the initial acetylene conversion rate dropped to 90%, and the ethylene selectivity dropped to 97%.
[0078] Example 4
[0079] (1) Commercial Si3N4 powder, carboxymethyl cellulose, starch, and deionized water are mixed and kneaded in a certain mass fraction ratio of Si3N4 powder: carboxymethyl cellulose: starch: deionized water = 50:5:5:50; the obtained kneaded product is extruded into cylindrical strips with a particle size of 2 mm by an extruder; the obtained cylindrical strips are initially dried at room temperature and then cut into 3 mm long particles; the obtained long particles are dried at 100°C for 16 hours in a microwave oven with a vacuum degree of 1000 Pa; the dried sample is calcined at 600°C for 4 hours using a Joule heater to obtain porous silicon nitride; the porous silicon nitride has a compressive strength of 36 N / cm and a specific surface area of 170 m 2 / g, the most probable pore diameter is 104nm, the pore volume is 0.40mL / g, and the crystal structure is anatase type.
[0080] (2) Weigh 4.0 g of copper sulfate, 4.43 g of palladium chloride, and 3.5 g of porous silicon nitride, add 15 ml of acetone, and stir for 1.5 h to mix thoroughly;
[0081] (3) placing the mixture at 70° C. for 2 h, filtering the solution until it becomes clear and transparent to obtain a mixture;
[0082] (4) subjecting the mixture to microwave heating and drying at 120° C. and 2000 Pa for 15 h;
[0083] (5) The dried mixture was heated at 10 °C min-1 using a Joule heater under a nitrogen atmosphere. -1 The heating rate was increased to 800 °C for high temperature treatment for 14 h;
[0084] (6) cooling the catalyst after the high temperature treatment to room temperature and washing it three times with hydrogen peroxide;
[0085] (7) subjecting the washed catalyst to microwave drying at 120° C., 2000 Pa for 15 h, and grinding the catalyst to a particle size of 10 mesh;
[0086] (8) Evaluation of acetylene hydrogenation reaction in a fixed bed reactor: Acetylene hydrogenation reaction at 200 °C, acetylene space velocity 150 h -1 , the reaction was carried out under the condition that the volume ratio of hydrogen to acetylene was 1:1, the raw gas also contained a carrier gas and C2H4, and the carrier gas was nitrogen; (the volume ratio of hydrogen to acetylene to nitrogen to ethylene was 1:1:202:100) after the reaction, the catalyst performance was that the initial conversion rate of acetylene was 80%, the selectivity of ethylene was 99%, and after 100 hours, the initial conversion rate of acetylene was maintained at 80%, and the selectivity of ethylene was reduced to 98%.
[0087] Example 5
[0088] (1) Commercial Si3N4 powder, methyl cellulose, urea, and deionized water are mixed and kneaded in a certain mass fraction ratio of Si3N4 powder: methyl cellulose: urea: deionized water = 50:5:5:50; the obtained kneaded product is extruded into cylindrical strips with a particle size of 3 mm by an extruder; the obtained cylindrical strips are placed at room temperature for preliminary drying and then cut into 4 mm long particles; the obtained long particles are dried at 120°C for 18 h in a microwave oven with a vacuum degree of 1000 Pa; the dried sample is calcined at 600°C for 4 hours using a Joule heater to obtain porous silicon nitride; the porous silicon nitride has a compressive strength of 39 N / cm and a specific surface area of 165 m 2 / g, the most probable pore diameter is 105nm, the pore volume is 0.43mL / g, and the crystal structure is anatase type.
[0089] (2) Weigh 4.08 g zinc chloride, 5.5 g palladium chloride, and 4.6 g porous silicon nitride, add 15 ml deionized water, and stir for 1.5 h to mix thoroughly;
[0090] (3) placing the mixture at 90° C. for 1 h, filtering the solution until it becomes clear and transparent to obtain a mixture;
[0091] (4) subjecting the gel-like substance to microwave heating and drying treatment at 150° C. and 10,000 Pa for 11 h;
[0092] (5) The dried mixture was heated at 10 °C min-1 using a Joule heater under an argon atmosphere. -1 The heating rate was increased to 300 °C for high temperature treatment for 18 h;
[0093] (6) cooling the catalyst after the high temperature treatment to room temperature and washing it three times with cyclohexanol;
[0094] (7) The washed catalyst was subjected to microwave heating and drying at 150° C. and 10,000 Pa for 11 h, and the particle size thereof was ground to 80 mesh;
[0095] (8) Evaluation of acetylene hydrogenation reaction in a fixed bed reactor: Acetylene hydrogenation reaction at 170°C, acetylene space velocity 200h -1 , the reaction was carried out under the condition that the volume ratio of hydrogen to acetylene was 1.2:1, the raw gas also contained a carrier gas and C2H4, and the carrier gas was nitrogen (the volume ratio of hydrogen to acetylene to nitrogen to ethylene was 1.2:1:202:100); after the reaction, the catalyst performance was that the initial acetylene conversion rate was 80%, the ethylene selectivity was 99%, and after 100 hours, the initial acetylene conversion rate was maintained at 80%, and the ethylene selectivity was maintained at 99%.
[0096] Example 6
[0097] (1) Commercial Si3N4 powder, polyvinyl alcohol, wet metatitanic acid, and deionized water are mixed and kneaded in a certain mass fraction ratio of Si3N4 powder: polyvinyl alcohol: wet metatitanic acid: deionized water = 40:1:1:30; the obtained kneaded product is extruded into cylindrical strips with a particle size of 2.5 mm by an extruder; the obtained cylindrical strips are placed at room temperature for preliminary drying and then cut into 3 mm long particles; the obtained long particles are dried at 110°C for 18 h in a microwave oven with a vacuum degree of 1000 Pa; the dried sample is calcined at 800°C for 6 hours using a Joule heater to obtain porous silicon nitride; the porous silicon nitride has a compressive strength of 33 N / cm and a specific surface area of 178 m 2 / g, the most probable pore diameter is 106nm, the pore volume is 0.41mL / g, and the crystal structure is anatase type.
[0098] (2) Weigh 14.61 g of nickel nitrate, 8.866 g of palladium chloride, and 4 g of porous silicon nitride, add 15 ml of 20% sucrose solution (with water as solvent), and stir for 1.5 h to mix thoroughly;
[0099] (3) placing the mixture at 50° C. and standing for 2.5 h, until the solution becomes clear, filtering to obtain a mixture;
[0100] (4) subjecting the mixture to microwave heating and drying at 140° C. and 8000 Pa for 20 h;
[0101] (5) The dried mixture was heated at 10 °C min-1 using a Joule heater under an argon atmosphere. -1 The heating rate was increased to 1600℃ for high temperature treatment for 6h;
[0102] (6) cooling the catalyst after the high temperature treatment to room temperature and washing it three times with liquid ammonia;
[0103] (7) subjecting the washed catalyst to microwave drying at 140° C. and 8000 Pa for 20 h, and grinding the catalyst to a particle size of 20 mesh;
[0104] (8) Evaluation of acetylene hydrogenation reaction in a fixed bed reactor: Acetylene hydrogenation reaction at 300 °C, acetylene space velocity 300 h -1 , the reaction was carried out under the condition that the volume ratio of hydrogen to acetylene was 1:1, the raw gas also contained a carrier gas and C2H4, and the carrier gas was nitrogen (the volume ratio of hydrogen to acetylene to nitrogen to ethylene was 1:1:202:100); after the reaction, the catalyst performance was that the initial conversion rate of acetylene was 95%, the selectivity of ethylene was 99%, and after 100 hours, the initial conversion rate of acetylene was maintained at 95%, and the selectivity of ethylene was reduced to 99%.
[0105] Example 7
[0106] (1) Commercial Si3N4 powder, polyethylene glycol, ammonium carbonate and deionized water are mixed and kneaded in a certain mass fraction ratio of Si3N4 powder: polyethylene glycol: ammonium carbonate: deionized water = 50:5:5:50; the obtained kneaded product is extruded into cylindrical strips with a particle size of 2.5 mm by an extruder; the obtained cylindrical strips are placed at room temperature for preliminary drying and then cut into 3.5 mm long particles; the obtained long particles are dried at 120°C for 20 h in a microwave oven with a vacuum degree of 1000 Pa; the dried sample is calcined at 800°C for 6 hours using a Joule heater to obtain porous silicon nitride; the porous silicon nitride has a compressive strength of 38 N / cm and a specific surface area of 171 m2 / g, the most probable pore diameter is 108nm, the pore volume is 0.39mL / g, and the crystal structure is anatase type.
[0107] (2) Weigh 4.63 g of nickel carbonate, 6.916 g of palladium chloride, and 5 g of porous silicon nitride, add 15 ml of methanol solution, and stir for 1.5 h to mix thoroughly;
[0108] (3) placing the mixture at 90° C. and standing for 0.5 h, until the solution becomes clear, filtering to obtain a mixture;
[0109] (4) subjecting the mixture to microwave heating and drying at 140° C. and 9000 Pa for 17 h;
[0110] (5) The dried mixture was heated at 20°C min-1 using a Joule heater in a helium atmosphere. -1 The heating rate was increased to 1800℃ for high temperature treatment for 2h;
[0111] (6) cooling the catalyst after the high temperature treatment to room temperature and washing it three times with butanol;
[0112] (7) The washed catalyst was subjected to microwave heating and drying at 140° C. and 9000 Pa for 17 h, and the particle size was ground to 20 mesh;
[0113] (8) Evaluation of acetylene hydrogenation reaction in a fixed bed reactor: Acetylene hydrogenation reaction at 200 °C, acetylene space velocity 500 h -1 , the reaction was carried out under the condition that the volume ratio of hydrogen to acetylene was 1:1, the raw gas also contained a carrier gas and C2H4, and the carrier gas was nitrogen (the volume ratio of hydrogen to acetylene to nitrogen to ethylene was 1:1:202:100); after the reaction, the catalyst performance was that the initial acetylene conversion rate was 91%, the ethylene selectivity was 98%, and after 100 hours, the initial acetylene conversion rate dropped to 80%, and the ethylene selectivity was maintained at 98%.
[0114] Example 8
[0115] (1) Commercial Si3N4 powder, carboxymethyl cellulose, citric acid, and deionized water are mixed and kneaded in a certain mass fraction ratio of Si3N4 powder: carboxymethyl cellulose: citric acid: deionized water = 60:10:10:55; the obtained kneaded product is extruded into cylindrical strips with a particle size of 1.5 mm by an extruder; the obtained cylindrical strips are placed at room temperature for preliminary drying and then cut into 3 mm long particles; the obtained long particles are dried at 120°C in a microwave oven with a vacuum degree of 1000 Pa for 20 h; the dried sample is calcined at 900°C for 8 hours using a Joule heater to obtain porous silicon nitride; the porous silicon nitride has a compressive strength of 33 N / cm and a specific surface area of 178 m2 / g, the most probable pore diameter is 99nm, the pore volume is 0.37mL / g, and the crystal structure is anatase type.
[0116] (2) Weigh 6.48 g of sodium chromate, 7.09 g of palladium chloride, and 2.8 g of porous silicon nitride, add 15 ml of ethanol solution, and stir for 1.5 h to mix thoroughly;
[0117] (3) placing the mixture at 35° C. for 3 h, and filtering the solution until it becomes clear and transparent to obtain a mixture;
[0118] (4) subjecting the mixture to microwave heating and drying at 140° C. and 6000 Pa for 18 h;
[0119] (5) The dried mixture was heated at 10°C min-1 using a Joule heater in a helium atmosphere. -1 The heating rate was increased to 800℃ for high temperature treatment for 10h;
[0120] (6) cooling the catalyst after the high temperature treatment to room temperature and washing it three times with propanol;
[0121] (7) The washed catalyst was subjected to microwave heating and drying at 140° C. and 6000 Pa for 18 h, and the particle size was ground to 20 mesh;
[0122] (8) Evaluation of acetylene hydrogenation reaction in a fixed bed reactor: Acetylene hydrogenation reaction at 160°C, acetylene space velocity 600h -1 , the reaction was carried out under the condition that the volume ratio of hydrogen to acetylene was 0.8:1, the raw gas also contained a carrier gas and C2H4, and the carrier gas was nitrogen (the volume ratio of hydrogen to acetylene to nitrogen to ethylene was 0.8:1:202:100); after the reaction, the catalyst performance was that the initial acetylene conversion rate was 88%, the ethylene selectivity was 99%, and after 100 hours, the initial acetylene conversion rate dropped to 86%, and the ethylene selectivity was maintained at 99%.
[0123] Example 9
[0124] (1) Commercial Si3N4 powder, polyethylene glycol, nitric acid, and deionized water are mixed and kneaded in a certain mass fraction ratio of Si3N4 powder: polyethylene glycol: nitric acid: deionized water = 40:1:1:30; the obtained kneaded product is extruded into cylindrical strips with a particle size of 3 mm by an extruder; the obtained cylindrical strips are initially dried at room temperature and then cut into 4 mm long particles; the obtained long particles are dried at 110°C for 10 h in a microwave oven with a vacuum degree of 1000 Pa; the dried sample is calcined at 120°C for 24 hours using a Joule heater to obtain porous silicon nitride; the porous silicon nitride has a compressive strength of 30 N / cm and a specific surface area of 168 m 2 / g, the most probable pore diameter is 97nm, the pore volume is 0.33mL / g, and the crystal structure is anatase type.
[0125] (2) Weigh 8.36 g of rhodium chloride, 7.09 g of palladium chloride, and 1.40 g of porous silicon nitride, add 15 ml of deionized water, and stir for 1.5 h to mix thoroughly;
[0126] (3) placing the mixture at 50°C for 2.5 hours to turn it into a gel-like substance;
[0127] (4) subjecting the mixture to microwave heating and drying at 140° C. and 8000 Pa for 20 h;
[0128] (5) The dried mixture was heated at 10 °C min-1 using a Joule heater under a nitrogen atmosphere. -1 The heating rate was increased to 1600℃ for high temperature treatment for 6h;
[0129] (6) cooling the catalyst after the high temperature treatment to room temperature and washing it with acetone three times;
[0130] (7) subjecting the washed catalyst to microwave drying at 140° C. and 8000 Pa for 20 h, and grinding the catalyst to a particle size of 20 mesh;
[0131] (8) Evaluation of acetylene hydrogenation reaction in a fixed bed reactor: Acetylene hydrogenation reaction at 170°C, acetylene space velocity 2000h -1 , the reaction was carried out under the condition that the volume ratio of hydrogen to acetylene was 0.8:1, the raw gas also contained a carrier gas and C2H4, and the carrier gas was nitrogen (the volume ratio of hydrogen to acetylene to nitrogen to ethylene was 0.8:1:202:100); after the reaction, the catalyst performance was that the initial acetylene conversion rate was 88%, the ethylene selectivity was 99%, and after 100 hours, the initial acetylene conversion rate dropped to 79%, and the ethylene selectivity was maintained at 99%.
[0132] Example 10
[0133] (1) Commercial Si3N4 powder, polyvinyl alcohol, glycerol, and deionized water are mixed and kneaded in a certain mass fraction ratio of Si3N4 powder: polyvinyl alcohol: glycerol: deionized water = 50:5:5:50; the obtained kneaded product is extruded into cylindrical strips with a particle size of 2 mm by an extruder; the obtained cylindrical strips are placed at room temperature for preliminary drying and then cut into 3.5 mm long particles; the obtained long particles are dried at 110°C for 16 hours in a microwave oven with a vacuum degree of 1000 Pa; the dried sample is calcined at 700°C for 8 hours using a Joule heater to obtain porous silicon nitride; the porous silicon nitride has a compressive strength of 36 N / cm and a specific surface area of 172 m 2 / g, the most probable pore diameter is 103nm, the pore volume is 0.35mL / g, and the crystal structure is anatase type.
[0134] (2) Weigh 11.56 g of rhodium nitrate, 7.09 g of palladium chloride, and 3.0 g of porous silicon nitride, add 15 ml of starch solution, and stir for 1.5 h to mix thoroughly;
[0135] (3) The mixture was placed at 30° C. and allowed to stand for 2.5 h. When the solution became clear, it was filtered to obtain a mixture.
[0136] (4) subjecting the mixture to microwave heating and drying at 140° C. and 10,000 Pa for 10 h;
[0137] (5) The dried mixture was heated at 20°C min-1 using a Joule heater in a helium atmosphere. -1 The heating rate was increased to 1600℃ for high temperature treatment for 6h;
[0138] (6) cooling the catalyst after the high temperature treatment to room temperature and washing it three times with aqueous ammonia;
[0139] (7) subjecting the washed catalyst to microwave drying at 140° C. and 10,000 Pa for 10 h, and grinding the catalyst to a particle size of 20 mesh;
[0140] (8) Evaluation of acetylene hydrogenation reaction in a fixed bed reactor: Acetylene hydrogenation reaction at 300 °C, acetylene space velocity 800 h -1 , the reaction was carried out under the condition that the volume ratio of hydrogen to acetylene was 1.2:1, the raw gas also contained a carrier gas and C2H4, and the carrier gas was nitrogen (the volume ratio of hydrogen to acetylene to nitrogen to ethylene was 1.2:1:200:100); after the reaction, the catalyst performance was that the initial acetylene conversion rate was 88%, the ethylene selectivity was 99%, and after 100 hours, the initial acetylene conversion rate dropped to 80%, and the ethylene selectivity was maintained at 99%.
[0141] Comparative Example 1
[0142] (1) Commercial Si3N4 powder, polyvinyl alcohol, glycerol, and deionized water are mixed and kneaded in a certain mass fraction ratio of Si3N4 powder: polyvinyl alcohol: glycerol: deionized water = 50:5:5:50; the obtained kneaded product is extruded into cylindrical strips with a particle size of 2 mm by an extruder; the obtained cylindrical strips are initially dried at room temperature and then cut into 3 mm long particles; the obtained long particles are dried at 80°C for 10 h in a microwave oven with a vacuum degree of 1000 Pa; the dried sample is calcined at 350°C for 2 hours using a Joule heater to obtain porous silicon nitride; the porous silicon nitride has a compressive strength of 35 N / cm and a specific surface area of 175 m 2 / g, the most probable pore size is 100nm, the pore volume is 0.35mL / g, and the crystal structure is anatase;
[0143] (2) Weigh 8.865 g of palladium chloride and 7 g of porous silicon nitride, add 10 ml of deionized water, and stir for 2 h to mix thoroughly;
[0144] (3) placing the mixture at 60° C. for 1 h, and filtering the solution until it becomes clear and transparent to obtain a mixture;
[0145] (4) subjecting the mixture to microwave heating and drying at 110° C. and 10,000 Pa for 2 h;
[0146] (5) The dried mixture was heated at 10 °C min-1 using a Joule heater under a nitrogen atmosphere. -1 The heating rate was increased to 1100℃ for high temperature treatment for 2h;
[0147] (6) Cooling the treated catalyst to room temperature and washing it three times with deionized water;
[0148] (7) The washed catalyst was subjected to microwave heating and drying at 110° C. and 10,000 Pa for 2 h, and the particle size was ground to 20 mesh;
[0149] (8) Evaluation of acetylene hydrogenation reaction in a fixed bed reactor: Acetylene hydrogenation reaction at 220°C, acetylene space velocity 120h -1 , the reaction was carried out under the condition that the volume ratio of hydrogen to acetylene was 1:1.2, the raw gas also contained a carrier gas and C2H4, and the carrier gas was nitrogen (the volume ratio of hydrogen to acetylene to nitrogen to ethylene was 1:1.2:200:100); after the reaction, the catalyst performance was that the initial acetylene conversion rate was 55%, the ethylene selectivity was 60%, and after 100 hours, the initial acetylene conversion rate dropped to 30%, and the ethylene selectivity dropped to 45%.
[0150] Comparative Example 2
[0151] (1) Commercial Si3N4 powder, polyvinyl alcohol, glycerol, and deionized water are mixed and kneaded in a certain mass fraction ratio of Si3N4 powder: polyvinyl alcohol: glycerol: deionized water = 40:1:1:30; the obtained kneaded product is extruded into cylindrical strips with a particle size of 1.5 mm by an extruder; the obtained cylindrical strips are placed at room temperature for preliminary drying and then cut into 3 mm long particles; the obtained long particles are dried at 90°C for 12 h in a microwave oven with a vacuum degree of 1000 Pa; the dried sample is calcined at 400°C for 1 hour using a Joule heater to obtain porous silicon nitride; the porous silicon nitride has a compressive strength of 32 N / cm and a specific surface area of 165 m 2 / g, the most probable pore diameter is 95nm, the pore volume is 0.38mL / g, and the crystal structure is anatase type.
[0152] (2) Weigh 7.0928 g of palladium chloride and 4.2 g of porous silicon nitride, add 12 ml of deionized water, and stir for 1.5 h to mix thoroughly;
[0153] (3) placing the mixture at 90° C. and standing for 0.5 h, until the solution becomes clear, filtering to obtain a mixture;
[0154] (4) subjecting the mixture to microwave heating and drying at 80° C. and 1000 Pa for 12 h;
[0155] (5) The dried mixture was heated at 10°C min-1 using a Joule heater in a helium atmosphere. -1 The heating rate was increased to 1300℃ for high temperature treatment for 2.5h;
[0156] (6) cooling the catalyst after the high temperature treatment to room temperature and washing it three times with ethanol;
[0157] (7) The washed catalyst was subjected to microwave heating and drying at 80° C. and 1000 Pa for 12 h, and the particle size was ground to 30 mesh;
[0158] (8) Evaluation of acetylene hydrogenation reaction in a fixed bed reactor: Acetylene hydrogenation reaction at 200 °C, acetylene space velocity 100 h -1 , the reaction was carried out under the condition that the volume ratio of hydrogen to acetylene was 1:1, the raw gas also contained a carrier gas and C2H4, and the carrier gas was nitrogen (the volume ratio of hydrogen to acetylene to nitrogen to ethylene was 1:1:202:100); after the reaction, the catalyst performance was that the initial acetylene conversion rate was 55%, the ethylene selectivity was 68%, and after 100 hours, the initial acetylene conversion rate dropped to 50%, and the ethylene selectivity dropped to 67%.
Claims
1. A method for preparing a porous silicon nitride supported Pd-M catalyst, wherein the M is selected from at least one of Cu, Zn, Ag, Ni, Cr, and Ru, characterized in that: The preparation method comprises the following steps: 1) Obtaining porous silicon nitride: mixing silicon nitride powder with a binder, an auxiliary agent and a solvent, kneading, and then extruding, air-drying, cutting, drying and calcining to obtain porous silicon nitride; the binder is selected from one or more of polyvinyl alcohol, polyethylene glycol, carboxymethyl cellulose and methyl cellulose; the auxiliary agent is selected from one or more of glycerol, starch, urea, wet metatitanic acid, ammonium carbonate, citric acid and nitric acid; the solvent is deionized water; the mass ratio of the silicon nitride powder, the binder, the auxiliary agent and the solvent is 40-60:1-10:1-10:30-55; 2) fully mixing the M-containing precursor with palladium chloride, the porous silicon nitride obtained in step 1), and solvent A, and stirring evenly to obtain a mixture 1; 3) leaving the mixture 1 obtained in step 2) to stand until the solution becomes clear and transparent, filtering to obtain a mixture 2; 4) subjecting the mixture 2 obtained in step 3) to microwave heating and drying to obtain a drying product; 5) subjecting the dried product obtained in step 4) to high temperature treatment using a Joule heater, cooling to room temperature, and washing with solvent B to obtain a high temperature treated product; 6) The high temperature treatment product obtained in step 5) is subjected to microwave heating and drying, and ground to obtain a porous silicon nitride supported Pd-M catalyst.
2. The preparation method according to claim 1, characterized in that: The method for preparing the porous silicon nitride comprises the following steps: Step a: Weigh a certain amount of commercial silicon nitride powder and a binder, mix them evenly, add an auxiliary agent and a solvent and knead them; Step b: Extruding the kneaded product obtained in step a into a long strip through an extruder; Step c: placing the strips obtained in step b at room temperature for preliminary drying and then cutting them into strips of a certain length; Step d: drying the strip obtained in step c; Step e: placing the dried sample in step d in a Joule heating apparatus, calcining at a temperature of 350 to 1000° C. for 1 to 10 hours to obtain porous silicon nitride.
3. The preparation method according to claim 2, characterized in that: The molar ratio of N:Si in the commercial silicon nitride is 4:
3.
4. The preparation method according to claim 1, characterized in that: In step 2), the copper-containing precursor is selected from one or more of copper acetate, copper chloride, copper nitrate and copper sulfate; the zinc-containing precursor is selected from one or more of zinc oxide, zinc chloride, zinc acetate, zinc carbonate, zinc nitrate and zinc sulfate; the silver-containing precursor is selected from one or more of silver nitrate, silver oxide, silver sulfate, silver chloride, silver ammonia solution and silver acetylacetonate; the nickel-containing precursor is selected from one or more of nickel chloride, nickel nitrate, nickel carbonate, nickel hydroxide, nickel oxalate and nickel sulfate; the chromium-containing precursor is selected from one or more of sodium chromate, potassium chromate, chromium chloride and chromium sulfate; the rhodium-containing precursor is selected from one or more of rhodium chloride, rhodium nitrate and rhodium acetylacetonate.
5. The preparation method according to claim 1, characterized in that: The M-containing precursor, palladium chloride and porous silicon nitride described in step 2) are added according to the element molar ratio of M:Pd:N=1:1:0.5-5.
6. The preparation method according to claim 1, characterized in that: The solvent A described in step 2) is selected from water, methanol, ethanol, acetone, sucrose aqueous solution, and starch aqueous solution.
7. The preparation method according to claim 1, characterized in that: Step 3) The mixture is allowed to stand at a temperature of room temperature to 90° C. for a time of 0.5 to 3 hours.
8. The preparation method according to claim 1, characterized in that: The temperature of the high temperature treatment in step 5) is 300-1800° C., the time of the high temperature treatment is 1-30 hours, and the atmosphere of the high temperature treatment is an inert atmosphere.
9. A porous silicon nitride supported Pd-M catalyst prepared according to the preparation method of any one of claims 1 to 8.
10. Use of the porous silicon nitride supported Pd-M catalyst as claimed in claim 9 in the selective hydrogenation of acetylene to ethylene.
Citation Information
Patent Citations
High-dispersion transition metal catalyst anchored to silicon nitride and preparation method and application thereof
CN114433246A
Cu / silicon nitride catalyst and preparation method and application thereof
CN116273136A
Hydrogenation catalyst preparation, hydrogenation catalyst and application
CN106861691A
Fischer-Tropsch Synthesis catalyst containing nitride carrier and preparation method and application thereof
CN107185572A
Preparation method of Pd-M-based metal catalyst for high-purity acetylene hydrogenation for preparing ethylene, and method for preparing ethylene
CN107362798A